(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The primary goal of retail operations similar to any other business is to make a profit by satisfying consumer needs. To achieve the goal and ensure competitiveness retail enterprises need to carry out their operations as efficiently as possible by applying the latest, most modern work organisation methods. Work efficiency can be achieved by reducing supply chain costs which in turn can be achieved through successful cooperation among all the parties involved. Efficient Consumer Response (ECR) is not just a new approach to process organisation in retail trade but affects all business processes as a whole taking them to a totally new and much higher level, thereby ensuring an increase in customer satisfaction and loyalty levels. The aim of the present research is to review the latest scientific literature on ECR, understand its working principles and carry out a survey of experts in order to ascertain the level of application of ECR in retail enterprises in the Baltic States and put forward recommendations for the enhancement of application of ECR.